TOWARDS EFFICIENT SOLAR LIGHT IN WASTEWATER TREATMENT: PHOTOCATALYTIC DEGRADATION OF ORGANIC CONTAMINANTS OVER DEFECT-RICH TITANIA - Hendra Saputera, Wibawa
Heterogeneous photocatalysis is a promising technique for waste water treatment. Titanium dioxide (TiO2) is the most used catalyst due to its chemical stability, high photocatalytic activity, non-toxicity and low price. Recently, modifications of TiO2 have been investigated to obtain better photocatalytic activity, i.e. generate oxygen vacancies to enhance visible light sensitivity and doping with noble metals to accelerate electron transfer reaction. This thesis describes the synthesis and characterization of defect sites in titanium dioxide and application in the wastewater treatment field. The first part of this work is emphasized on the preparation and characterization of TiO2/Ti2O3 binary mixtures and its use in the photocatalytic degradation of both methyl orange and methylene blue by ultraviolet (UV) irradiation. Materials were synthesized by means of physical mixtures using TiO2 anatase phase and Ti2O3. By controlling the calcination temperature, materials with different morphology, crystallinity and surface area were obtained. The binary mixture annealed at 600oC is the most active catalyst in comparison to other calcination temperatures. In order to increase the TiO2 photo-efficiency, in particular in the visible light region, the binary mixture was equipped with different metals, such as platinum (Pt), gold (Au) and copper (Cu). The mixture containing Pt showed high photocatalytic activity while the presence of both gold and copper induced less promotion of activity. The second part of this work is focused on preparation and characterization of hydrogenated commercial TiO2, e.g. anatase, rutile, and a mix of both rutile and anatase (P25). Again by controlling the calcination temperature during the hydrogenation process, P25 annealed at 500oC show the best photocatalytic activity. Platinum promoted TiO2 anatase annealed at 600oC shows a big improvement as compared to P25 annealed at 500oC. Generally, the presence of rutile phase, anatase phase and defect-rich titania enhances photocatalytic activity most effectively.